Entrepreneurship: The Case of Ecuador - Morales-Molina, Tania (2021)
In recent decades, entrepreneurship has experienced a significant increase worldwide, being considered as an important tool to improve the economic growth of a country. This article aims to present an overview of the current situation of entrepreneurship at both national and local levels. The methodology used was descriptive, also a literature review was conducted, the data analyzed came from the National Institute of Statistics and Censuses of the directory of companies for the period 2013–2016, the number of enterprises at the level of Ecuador and specific by province was analyzed. After the analysis, it was concluded that there is a significant increase in micro-enterprises throughout the country, especially in the provinces of Pichincha and Guayas.